2019
DOI: 10.1002/asia.201801834
|View full text |Cite
|
Sign up to set email alerts
|

Isoselective Ring‐Opening Polymerization of rac‐Lactide Catalyzed by Sodium/potassium Tetradentate Aminobisphenolate Ion‐paired Complexes

Abstract: Twos odium/potassium tetradentate aminobisphenolate ion-paired complexes were synthesized and structurally characterized. These ion-paired complexesa re efficient catalysts for the ring-opening polymerization of rac-lactide (rac-LA) in the presence of 5equivalents BnOH as an initiator and the side reactiono fe pimerization can be suppressed well at low temperatures. The polymerizations are controllable, affording polylactidesw ith desirable molecular weights and narrow molecular weightd istributions;t he highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…[14] Among alkali metals, potassium compounds are actively studied for various applications such as precursors for the metalorganic chemical vapor deposition (CVD) processes of the ferroelectric (K,Na)NbO 3, [15] the atomic layer deposition (ALD) of potassium oxide, [16] sol-gel processes to produce hybrid organic-inorganic materials [17] and in catalytic processes such as the ring-opening polymerization. [18][19][20] Potassium ion has a large ionic radius (r 6-coord = 1.51 Å), [13] which is responsible for interesting coordination moieties giving rise, in function of the coordinating ligands to extended oligomeric or polymeric network. [21][22][23] Former studies have shown that glymes play a crucial role in stabilizing complexes of alkaline-earth, [24][25][26][27][28] transition [29,30] and rare-earth metals [31,32] through oxygen-ion complexation.…”
Section: Introductionmentioning
confidence: 99%
“…[14] Among alkali metals, potassium compounds are actively studied for various applications such as precursors for the metalorganic chemical vapor deposition (CVD) processes of the ferroelectric (K,Na)NbO 3, [15] the atomic layer deposition (ALD) of potassium oxide, [16] sol-gel processes to produce hybrid organic-inorganic materials [17] and in catalytic processes such as the ring-opening polymerization. [18][19][20] Potassium ion has a large ionic radius (r 6-coord = 1.51 Å), [13] which is responsible for interesting coordination moieties giving rise, in function of the coordinating ligands to extended oligomeric or polymeric network. [21][22][23] Former studies have shown that glymes play a crucial role in stabilizing complexes of alkaline-earth, [24][25][26][27][28] transition [29,30] and rare-earth metals [31,32] through oxygen-ion complexation.…”
Section: Introductionmentioning
confidence: 99%
“…Improved polymerization rates were obtained with catalysts based on indium, [35,36] yttrium, [37,38] group 4m etals, [39,40] zinc, [41][42][43][44][45] and alkali metals. [46,47] Some of these catalysts were even found to exhibit isoselectivities that approacht hose reported for the aluminumc omplexes. The development of highly active catalysts that are also highly isoselective is still as ignificant challenge in the field of ROP catalysis.…”
Section: Introductionmentioning
confidence: 80%
“…Yet, these complexes also suffer from low polymerization rates and low turnover numbers, which prevent the production of high‐molecular‐weight PLA. Improved polymerization rates were obtained with catalysts based on indium, [35, 36] yttrium, [37, 38] group 4 metals, [39, 40] zinc, [41–45] and alkali metals [46, 47] . Some of these catalysts were even found to exhibit isoselectivities that approach those reported for the aluminum complexes.…”
Section: Introductionmentioning
confidence: 93%
“…Therefore, low or nontoxic metal catalyst for the ROP of cyclic esters are strongly needed . Group 1 and 2 metals as well as zinc are promising candidates due to their low cost, remarkably high activity, and minimal toxicity, and among these metals, magnesium complexes are of particular interest for technical applications due to their high activity toward the ROP of cyclic esters. The last two decades have witnessed the development of highly active mononuclear magnesium catalysts containing a large variety of monodentate, bidentate, tridentate, and tetradentate , ligands. In addition, dinuclear complexes containing bridging ligands as well as multinuclear complexes have been shown to be active catalysts for the ROP of cyclic esters.…”
Section: Introductionmentioning
confidence: 99%